Side by Side: A Comparative Examination of the Role of Gender for Ethiopian Smallholder Farmers at the Agriculture-Nutrition Nexus - Min-Barron, Marion. (Tufts University. Tisch Library., 2019)
Gender has increasingly become mainstreamed in agriculture-nutrition program design and policy formation. This dissertation sought to understand how gender dynamics affect the planning and implementation of agriculture development programs that are meant to benefit nutrition. Through three distinct studies all conducted in the context of the Ethiopian nutrition program, Empowering New Generations to Improve Nutrition and Economic Opportunities (ENGINE), this dissertation compared women and men's experiences regarding behavior change and empowerment in agriculture and also assessed the validity of a recently developed empowerment metric. The first study was a gendered comparison of the process of nutrition behavior change within the context of nutrition-sensitive and nutrition-specific program platforms. Through a unique participatory approach, this study examined the behavior change stages through the 'Message Train', a conceptual framework developed and tested for this study which deconstructed sustainable behavior change into six distinct sub-processes. Women consistently had more contact with nutrition-specific messages and shared them more frequently than men. Contact and sharing of nutrition-sensitive messages by women regarding agricultural practices was low compared to nutrition-sensitive messages related to WASH. Results suggest that behavior change communication strategies within the context of nutrition-specific and sensitive programs warrant focused attention to the different ways in which women and men receive, internalize, share and adopt different nutrition messages both individually and collectively. The second study determined how smallholder farming women and men differ in their definitions of empowerment in agriculture. It also assessed the emic content validity of the Abbreviated-Women's Empowerment in Agriculture Index (A-WEAI) by comparing the emic definitions to empowerment domains operationalized in the A-WEAI. This qualitative study found that, for women, empowerment was being able to perform activities that required bravery in the face of discriminatory gender norms. For men, empowerment came through the fulfillment of their societal gender role. Men's emic definition of empowerment appeared to have a slightly closer alignment, compared to women's, with the etic A-WEAI definition of empowerment. For both genders, however, the A-WEAI domains of resources, leadership and time had little to no content validity in our study sample. The A-WEAI also omitted several concepts that respondents felt were pertinent to empowerment, including individual levels of self- efficacy, ability to multi-task, and culturally related sources of empowerment such as recognition by community. Results highlighted how the inclusion of emic perspectives in empowerment metrics can improve the design of programs that address the 'felt' barriers to empowerment as well as reinforce the achievement of a subjective state of empowerment. The last study assessed the etic content validity of the A-WEAI using qualitative interviews, household survey data and an online expert panel survey. Based on the criteria of content relevance, representativeness, and technical quality, the study found mixed results of content validity adequacy. All experts judged the A-WEAI items to be excellent in relevance while also suggesting that important domains such as knowledge and access to information were omitted. Individual cognitive debriefing interviews suggested that several items and item responses, such as the meaning of 'asset ownership', were not interpreted by subjects as index developers intended. For women, the Cronbach's alpha for the production, income and leadership domains was higher than 0.65, indicating acceptable internal reliability. The resources domain, however, was not homogenous with other items in the scale, suggesting that this domain may not be pertinent to women's empowerment within our study sample. This dissertation identified the value of communication between genders as a potentially effective and sustainable vehicle for behavior change. It also highlighted the need for definition clarity in empowerment research as well as the inclusion of context specific domains and operationalizations within empowerment measurement. Together, the three studies elucidated the necessity for further research that examines effects of gender specific programming on men as well as further emic and etic based validation of gender indices, such as the A-WEAI, in different contexts.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Food Policy & Applied Nutrition.; Advisor: Jennifer Coates.; Committee: Shibani Ghosh, John Maluccio, and Beatrice Rogers.; Keywords: Nutrition, and Gender studies.